Analysis of Using Telemedicine Application for Pregnant Women During COVID-19 Pandemic Based on ISO 9241-11 - Zakiya, Nurani Zulfa; Cahya, Muhammad Ardian; Handayani, Samsriyaningsih (Journal of Maternal and Child Health, 2023)
Background: The COVID-19 pandemic has affected the performance of several sectors, one of which is the quality of maternal and child health services. One of the factors contributing to the decline in the quality of maternal and child health services is limited access during the COVID-19 pandemic. Telemedicine is here as one of the answers to overcome the problem of limited access to health services during the COVID-19 pandemic. This study aims to analyze the use of telemedicine applications by pregnant women during the COVID-19 pandemic using the ISO 9241-11 framework. Subjects and Method: This research method is an observational study with a descriptive approach to analyze usability in three measurement aspects namely effectiveness, efficiency, and satisfaction. The number of samples used was 42 pregnant women who had used telemedicine applications that had been determined during the COVID-19 period with a sampling technique using random sampling. The instrument used is an adaptation of the Standardized Usability Questionnaire (SUQ) which will be analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) technique to determine the usability score of the application. Results: Based on the results of the Structural Equation Model-Partial Least Square (SEM-PLS) analysis, the ISO 9241-11 model has a goodness-of-fit model with an R-square value of 0.760 and a Q-square value of 0.577 with a Goodness of Fit (GoF) of 0.780. The effectiveness variable has a significant effect on the usability variable of the Teman Bumil application at a significance level of 5% with a statistical T value of 1,955. There is not enough evidence for the efficiency and satisfaction variables to say they have a significant effect on the usability of the Teman Bumil application at a 5% significance level with T-statistic values of 0.866 and 1.452. The usability score for the Friends Pregnant application is 44.45. Conclusion: The usability score obtained by the Teman Bumil application is 44.45, which means that Sahabat Bumil application has not been accepted by users as a system product that can help effectively, efficiently and satisfactorily. Keywords: telemedicine, pregnant women, COVID-19, ISO 9241-11, usability. Correspondence:Nurani Zulfa Zakiya, Midwifery Program Study, Faculty of Medicine, Universitas Airlangga, Indonesia. Jl. Mayjen Prof. Dr. Moestopo No. 47, Pacar Kembang, Tambaksari, Surabaya 60132, East Java . Email: nurani.zulfa.zakiya-2019@fk.unair.ac.id. Mobile: +6281217621007.